PERLINDUNGAN DATA PRIBADI SESEORANG YANG SUDAH MENINGGAL BERDASARKAN UNDANG-UNDANG NOMOR 27 TAHUN 2022 TENTANG PERLINDUNGAN DATA PRIBADI - Manik, Damianus Sihol Marito; Firdaus, Emilda; Junaidi, Junaidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Personal data protection is very important in today's modern world. Personal data isconfidential and sensitive information about a person. In the personal data protection law, aperson's personal data must be protected from unauthorized access or misuse. However, thequestion that arises is how is the protection of personal data of a deceased person regulatedin the personal data protection law? In fact, the protection of a deceased person's personaldata is actually also very important to consider. Even though the person has passed away,their personal data must still be kept confidential as it can still be used by irresponsibleparties. In many countries, personal data protection laws regulate the protection of personaldata of deceased persons. In Indonesia, the protection of personal data of deceased personsdoes not yet have a clear legal umbrella. The protection of the personal data of a deceasedperson is important to prevent misuse of data that can harm the family or other living partiesand the state. The personal data of someone who has died can be used for bad purposes,such as identity theft or fraud.This research aims to find out and explain how the protection of personal data of adeceased person in terms of respect for individual privacy. Even though the person is dead,there is still a right to privacy that must be respected. In this case, the government andrelated institutions must ensure that Law No. 27 of 2022 on Personal Data Protection alsocovers the protection of personal data of deceased persons. In addition, it is important tosocialize and educate the public about the importance of protecting personal data, includingthe personal data of deceased persons. Thus, the protection of personal data of deceasedpersons is an important part of the overall protection of personal data. With cleararrangements and firmness in maintaining the confidentiality of the personal data ofdeceased individuals, it is hoped that it can prevent the misuse of personal data of deceasedindividuals which can harm many parties including the state.Keywords: Protection, Personal Data, Death